(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
The house fly, Musca domestica L, has been identified as a vector for a variety of human and animal illnesses. Eradication of such pests needs the help of insecticides which in turn has led to the growth in insecticides or insect repellents which are not only effective but are also non-toxic. In this paper, the anti-fly property of custard apple (Annona muricata) seeds has been shown against Musca domestica L. Firstly, oil was extracted from the custard apple seeds. Afterwards, sugar cubes were left untreated or coated with a fresh coat of custard apple seed oil. After 120 hours, the freshly treated sugar samples exhibited anti-fly property against the flies in this study. Moreover, spraying of a solution of custard apple seed oil and water led to death of many flies. It can thus be concluded that custard apple seed oil is a promising natural anti-fly agent and the abundance of custard apple seeds means that at an industrial scale such insecticide or insect repellent can be produced.